2023
DOI: 10.3390/bs13090755
|View full text |Cite
|
Sign up to set email alerts
|

Changing Decisions: The Interaction between Framing and Decoy Effects

Adolfo Di Crosta,
Anna Marin,
Rocco Palumbo
et al.

Abstract: Background: Cognitive biases are popular topics in psychology and marketing, as they refer to systematic cognitive tendencies in human thinking that deviate from logical and rational reasoning. The framing effect (FE) and the decoy effect (DE) are examples of cognitive biases that can influence decision making and consumer preferences. The FE involves how options are presented, while the DE involves the addition of a third option that influences the choice between the other two options. Methods: We investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 58 publications
(78 reference statements)
1
1
0
Order By: Relevance
“…Similar to Stoffel and colleagues [ 27 ], we find a distinct order effect, in that only presenting the monetary incentive first, followed by the decoy donation, heightened survey completion rates compared to reversed presentation. This is in line with another recent study that found the decoy effect is influenced by the framing of the decoy alternative [ 35 ]. In our experiment, the order effect exhibits a primacy bias, as individuals tend to consider the option listed first rather than last [ 36 ].…”
Section: Discussionsupporting
confidence: 93%
“…Similar to Stoffel and colleagues [ 27 ], we find a distinct order effect, in that only presenting the monetary incentive first, followed by the decoy donation, heightened survey completion rates compared to reversed presentation. This is in line with another recent study that found the decoy effect is influenced by the framing of the decoy alternative [ 35 ]. In our experiment, the order effect exhibits a primacy bias, as individuals tend to consider the option listed first rather than last [ 36 ].…”
Section: Discussionsupporting
confidence: 93%
“…Information framing is a theory-based persuasive communication strategy, aiming to facilitate changes in perception, judgment, attitude, and behavior by presenting equivalent appeals [25]. In the field of behavioral science, framing effects are often used to influence individual decision-making and behavioral preferences [26,27]. For example, by providing individuals with information framed around the benefits and public good nature of vaccines, it is possible to increase residents' intentions to get vaccinated [28].…”
Section: Attribute Framing Effect and Its Impact On Persuasionmentioning
confidence: 99%